Anandamide induces apoptosis in human endothelial cells: its regulation system and clinical implications - Yamaji, Kazuyo; Sarker, Krishna Pada; Kawahara, Koichi; Iino, Satoshi; Yamakuchi, Munekazu; Abeyama, Kazuhiro; Hashiguchi, Teruto; Maruyama, Ikuro (Thrombosis and Haemostasis, 2003)
Anandamide (AEA), an endogenous cannabinoid, is generated by macrophages during shock conditions, and is thought to be a causative mediator of septic shock. Thus, we hypothesized that AEA plays a crucial role in endothelial cell (EC) injury. Here, we demonstrate that AEA induces apoptosis in a time-and dose-dependent manner in human umbilical vein endothelial cells (HUVECs). AEA triggered phosphorylation of c-Jun NH2-terminal kinase (JNK) and p38 mitogen activated protein kinase. AEA also showed a marked increase of interleukin 1β–converting enzyme (ICE)CED-3 family protease (caspase-3) activity. AEA-induced EC death was inhibited by a selective vanilloid receptor 1 (VR1) antagonist, capsazepine, and was enhanced by a VR1 agonist, capsaicin, indicating that AEA induces apoptosis in ECs via VR1. In conclusion, we propose that AEA may play a crucial role in EC injury under conditions of shock, and that the use of inhibitors of the AEA regulation system may have a therapeutic effect under these conditions.
Keywords: Anandamide; endothelial cell; apoptosis; vanilloid receptor 1; endotoxin shock